Rancang Bangun Sistem Otomatisasi Pergantian Air Kolam Budidaya Ikan Nila Berdasarkan Parameter Kondisi Air Menggunakan Nodemcu ESP8266 - Cintya Nada Anjali; Moch Lutfi (INFORMAL: Informatics Journal, 2023)
Water quality in ponds is a physical factor that influences tilapia cultivation. In general, tilapia can grow at a degree of acidity (pH) 5-9 with a maximum air turbidity of 50NTU. Cases of tilapia death in GIP Housing Martopuro Village often occur due to a lack of attention in maintaining the quality of pond water. So with the case study method that aims to solve these problems a system is designed that can monitor water quality and automatic water changes based on water condition parameters through the "Nila Fish Care" application, the application is available on Google Playstore. The results of testing the average water pH is 6.37 and the average value of water turbidity is 35.96. With this system, that it can assist tilapia farmers in monitoring air quality remotely using an application and changing water automatically without human power